The Brazilian popular guitar: searching for possible definitions (Per Musi, 2018)
Due to our doctoral research on popular guitar education in Brazilian universities, we have encountered first the fundamental difficulty to understand and define the boundaries of what might be called popular guitar. In a second time, to add to this already complex set of meanings, the national character, trying to find answers, even if temporary, to what can be understood as the Brazilian popular guitar. For this, we traced three functions performed by the guitar in Brazilian music, in order to organize the understanding of its performance. This article is therefore the purpose of attending to the diversity and range of meanings attributable to the term so that its consequences can also be seen in the context of university education.